An analysis of foreshadowing in Stephen King's Rita Hayworth and Shawshank Redemption - Agni Dhiyaaul Lathifatul Hudayah; Rindu Handayani; Haiyudi Haiyudi (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2025)
ABSTRACT This study addresses readers’ confusion regarding the plot twist in Stephen King’s Rita Hayworth and Shawshank Redemption, particularly how the surprising ending is narratively constructed through foreshadowing. Although many readers are shocked by the conclusion, they often overlook how subtle narrative clues prepare them emotionally and intellectually for the climax. This study aims to explain how foreshadowing functions as an effective device in constructing the plot twist by analyzing both explicit and implicit forms of foreshadowing in the novella. Using a qualitative literary analysis approach, the study applies Gérard Genette’s (1980) theory of prolepsis. Data were collected through close reading, with the researchers acting as non-participant textual observer. The analysis involved narrative mapping, thematic coding, and systematic classification of foreshadowing elements into linguistic, symbolic, and structural categories, following qualitative observation procedures proposed by Moleong (2017). The findings identify 17 instances of foreshadowing, consisting of 12 implicit and 5 explicit cases. Key narrative elements such as the Rita Hayworth poster and the rock hammer illustrate that implicit foreshadowing plays a dominant role in subtly guiding readers toward the plot twist, while explicit foreshadowing provides clearer narrative signals. Overall, the study demonstrates that foreshadowing is central to the novella’s narrative coherence and the effectiveness of its surprise ending. Keywords: Foreshadowing; Stephen King; Rita Hayworth: Shawshank Redemption; Plot twist